The effectiveness of Table Mountain National Park Marine Protected Area in the conservation of rocky shore biodiversity - Baliwe, Ndiviwe Gabriel (Department of Biological Sciences, 2021)
Establishment of marine protected areas (MPAs) has intensified in recent years, and there are now over 6800 MPAs worldwide. However, there is a prominent need to assess their effectiveness in terms of protecting biodiversity. In Chapter 1, I provide the theoretical background to this dissertation and define its central goal, i.e., to assess the effectiveness of no-take (‘restricted') sections of the Table Mountain National Park MPA (TMNP MPA), relative to zones that are designated as ‘controlled', where harvesting can take place under national regulations. Chapter 2 compares the effectiveness of no-take versus harvested areas in the TMNP MPA in protecting the biodiversity of intertidal rocky shores. Surveys were conducted to compare (1) the densities and sizes of exploited species and rarely harvested species, and (2) community composition, between these two levels of protection. Some clear patterns emerged. Firstly, notake areas had significantly greater densities of the commonly harvested limpets Cymbula granatina, C. oculus and Scutellastra argenvillei, most obviously on sandstone ledges where abundances were greatest. In contrast, densities of the rarely harvested limpets, S. cochlear, S. longicosta and S. granularis did not differ in a manner reflecting protection levels. Secondly, C. granatina and S. argenvillei were significantly larger in no-take areas, although C. oculus displayed the opposite pattern. None of the rarely harvested limpets showed differences in sizes between protection levels. Thirdly, community composition differed significantly between protection levels. No-take areas were characterised by a greater abundance of commonly harvested limpets and mussels, while harvested areas were dominated by ephemeral and corticated algae, due to their release from grazing pressure by limpets. Chapter 3 focuses on a subset of the sites, all lying on the west coast and all comprising sandstone rocks. First, in a temporal comparison, I evaluated changes in densities and sizes of limpets and in community composition between historical data from 1970 and my sampling in 2017, at two sites where harvesting has intensified since 1970. This analysis showed three kinds of changes: (1) the appearance of alien species; (2) the effects of increased harvesting; and (3) the direct and indirect effects of these changes on other species. Secondly, to disentangle the effects of harvesting from those of alien invasions, I made spatial comparisons using my 2017 data, between two harvested sites and two sites in a no-take zone. One striking result was transformation of mid-shore zones by the appearance of the invasive Mediterranean mussel Mytilus galloprovincialis, and the indirect effects of this on the demography of the granular limpet Scutellastra granularis. Adults of this limpet have been excluded by the mussel, whereas juveniles find a secondary home on the shells of the mussel. In addition, harvesting has decimated the granite limpet Cymbula granatina and Argenville's limpet Scutellastra argenvillei. This has led to the proliferation of opportunistic seaweeds, such as Ulva spp., or corticated algae, notably Pachymenia orbitosa. The dual effects of alien invasive species and over-harvesting thus have major ecosystem effects. In chapter 4, densities of the limpet Cymbula granatina were manipulated at two sites within a fully-protected no-take area to generate four density levels ranging from zero to maximum natural densities, to evaluate the effects of harvesting this limpet on the community composition. Following removal or substantial thinning of C. granatina, community composition changed, cover of corticated and ephemeral algae increased and recruitment of C. granatina decreased. These outcomes were, however, dependent on the time frame considered, as algae underwent an annual cycle, and the effects of limpet removal were evident only during cooler months when the algae proliferated. All these effects have management implications. Chapter 5 provides an overview of the findings from this dissertation and their management implications. The major limitation of the dissertation is that interpretation of results was clouded by an absence of reliable data on actual harvesting rates as reflected in the numbers and activities of people operating in the restricted and controlled portions of the MPA, and of the efficiency with which law enforcement takes place. Nevertheless, strong evidence emerged that no-take areas within the MPA are effective means of conserving biodiversity, and the effects of harvesting deduced in Chapter 2 and 3 were verified by the experiment undertaken in Chapter 4, in which depletion of a dominant and commonly harvested limpet, Cymbula granatina, did yield algal proliferations like those evident in harvested portions of the park. The fact that this outcome was observed only at certain times of the year points to the need for studies and monitoring to be undertaken over sufficient time scales to produce meaningful results.